Autoimmune pancreatitis - Fan, Bo-Guang (Medknow Publications & Media Pvt Ltd, 2009)
Since the autoimmune pancreatitis was introduced in 1995, it has been recognized as a form of chronic pancreatitis, which is always associated with autoimmune manifestations. As the improvement of technical and instrumental made in ultrasonography, computed tomography and magnetic resonance imaging, the diagnoses of autoimmune pancreatitis is no longer such difficult. Even though the treatment of autoimmune pancreatitis is available with a conservative therapy, there are many points that are still unclearly. These have stimulated widespread interest in this disease from gastroenterologists, endoscopists, pathologists, and prevalent research. The present article provides with our better understanding of the diagnosis and treatment of autoimmune pancreatitis.